Affective organizational commitment and dispositional mindfulness as correlates of burnout in health care professionals. (2nd April 2016) - Voci, Alberto; Veneziani, Chiara A.; Metta, Martina
ABSTRACT: A study conducted on 98 Italian health professionals investigated the associations between mindfulness, organizational commitment, and burnout syndrome, controlling for the effect of potentially stressful events. Results showed that affective commitment and dispositional mindfulness were negatively associated with burnout. Dispositional mindfulness also moderated the relation between potentially stressful events and two burnout dimensions, emotional exhaustion and depersonalization. These findings suggest that affective commitment and dispositional mindfulness are important factors in protecting against the onset of burnout in healthcare professionals. Moreover, mindfulness seems to contain the adverse consequences of potentially stressful events.